Some comments on Jorink’s ‘Swammerdam, hoveling?’ - Anderson, Douglas (Studium, 2017)
In this paper a reaction is presented on an earlier article, published in Studium, devoted to the reputation of the 17th-century microscopist Johannes Swammerdam (1637-1680). It is argued that the picture sketched in that paper by Eric Jorink has some interpretations which can be questioned in the light of the available historical sources.